Child Fatality Individual Case Reports: A 24‐Year National State‐by‐State Review - Mantell, David M.; Chong, Natalie; Takeno, Todd; Pazdur, Michelle; Walker, Taylor (Child abuse review (Chichester, England : 1992), 2024)
This study focused on the content of 1186 Child Fatality Review Board individual case reports collected nationally over a 24‐year period (1995–2019). This information, in contrast to group data, may yield important insights into the causative factors, especially for child fatality resulting from neglect and inflicted injury. The reports were collected from six of the 50 states and evaluated for the quality and amount of information. They were also surveyed for data identifying causative factors for neglect and inflicted injury. Only 25 (2 per cent) of 1186 reports that are publicly available contained sufficient information about the four major causative factors—cause of death, prior child protection agency involvement by the family, evidence of professional negligence or error and family history of at‐risk circumstances. The 25 cases were then reviewed and coded for presence of information about these factors. The findings demonstrate the need for federal intervention to provide specific guidelines for the states to track their cases, to use a common nomenclature, to investigate common causative factors and to practice common reporting procedures. In this way, a robust national database can be developed.